Comparative study of four greenness assessment tools for selection of greenest analytical method for assay of hyoscine N-butyl bromide. Issue 3 (6th January 2021) - Gamal, Mohammed; Naguib, Ibrahim A.; Panda, Dibya Sundar; Abdallah, Fatma F.
Abstract : The competencies of four greenness assessment tools were tested. AGREE is the best greenness tool while NEMI is the poorest one. AGREE, GAPI, and ESA are reliable greenness tools. Abstract : Several assessment tools were recently introduced for the evaluation of the greenness of analytical methods. Each tool has advantages, disadvantages, and a unique assessment protocol. The final results obtained from each assessment tool may lead to a dissimilar conclusion about the selection of the greenest method, which makes the decision confusing as to which an assessment tool relies on. Accordingly, in this comparative case study, four greenness assessment tools—National Environmental Methods Index (NEMI), Eco-Scale Assessment (ESA), Green Analytical Procedure Index (GAPI), and Analytical GREEnness metric (AGREE)—were tested to evaluate 16 chromatographic methods described in the literature for the assessment of the commonly used antispasmodic drug Hyoscine N -butyl bromide (HNBB). The importance of applying more than one assessment tool when evaluating the greenness of analytical methods is explained in this study. Despite NEMI tool simplicity, it was the least effective in providing information about the analytical method as 14 out of 16 methods had the same NEMI pictogram. ESA and AGREE provided reliable numerical assessments that differed in their total scores whereas the total scores were out of 100 and 1 for each, respectively. AGREE has the merits over ESA with respect to automation and highlighting the weakest points in analytical techniques that need further improvements in terms of greenness. GAPI and AGREE provide fully descriptive three-colored pictograms. The main disadvantage of GAPI is complexity compared to NEMI and ESA. AGREE has the merits of simplicity and automation over GAPI. Based on the results, recommendations are made for ESA, GAPI, and AGREE tools, which provide reliable and precise results about the greenness of the method. Planning for the greenness of analytical methods should be assured before practical trials in a laboratory for reduction of chemical hazards released into the environment. Moreover, inclusion of the evaluation of greenness of analytical methods in method validation protocols is strongly recommended.